Serum Matrix Metalloproteinase-2, -7 and -9 (MMP-2, MMP-7, MMP-9) levels as Prognostic Markers in Patients with Colorectal Cancer - Kostova, Elena; Slaninka Miceska, Maja; Labachevski, Nikola; Jakjovski, Krume; Trojachanec, Jasmina; Atanasovska, Emilija; Janevski, Vlado; Selmani, Redzep; Petrushevska, Gordana; Janevska, Vesna (University of Sarajevo Faculty of Health Sciences, 2012)
Introduction: Matrix metalloproteinases are produced by tumour cells, hence, they may be associated with tumour progression including invasion, migration, angiogenesis and metastasis. Finding prognostic markers to better identify patients with higher risk for poor survival would be valuable in order to customize pre- and postoperative treatment as well as to enable closer follow-up of these patients. Aim of our study was to examineMMP-2, MMP-7 and MMP-9 serum levels and correlated them with pathological data such as stage of the colorectal cancer (CRC) and outcome.Methods: The investigation included 82 patients with operable CRC without distant metastases, who had underwent blood tests in order to determine the MMP-2, MMP-7 and MMP-9 serum levels in the following time periods: preoperatively, 3, 6, 9 and 12 months postoperatively.Results: The values of the investigated MMPs decrease postoperatively and start to increase 6 month later in patients of all stages of the disease, reaching the highest value 12 month postoperatively with statistically important differences of MMP-2, MMP-7 and MMP-7 serum levels in terms of disease staging and defined points of time. Analysis of the results showed that the MMP-2 serum levels obtained 3 and 12 months postoperatively,than MMP-7 serum levels 12 months postoperatively and the MMP-9 serum levels in all analyzed points in time were in significant association with the CRC patients’outcome.Conclusion: The MMP-2, MMP-7 and especially MMP-9 serum values could be important indicators for diagnosis of the patients with CRC and for monitoring of disease progression.